Soil & Water Assessment Tool (SWAT) simulated hydrological impacts of land use change from temperate grassland to energy crops: A case study in western UK. Issue 11 (26th July 2019) - Holder, Amanda J.; Rowe, Rebecca; McNamara, Niall P.; Donnison, Iain S.; McCalmont, Jon P.
Abstract: When considering the large‐scale deployment of bioenergy crops, it is important to understand the implication for ecosystem hydrological processes and the influences of crop type and location. Based on the potential for future land use change (LUC), the 10, 280 km 2 West Wales Water Framework Directive River Basin District (UK) was selected as a typical grassland dominated district, and the Soil & Water Assessment Tool (SWAT) hydrology model with a geographic information systems interface was used to investigate implications for different bioenergy deployment scenarios. The study area was delineated into 855 sub‐basins and 7, 108 hydrological response units based on rivers, soil type, land use, and slope. Changes in hydrological components for two bioenergy crops ( Miscanthus and short rotation coppice, SRC) planted on 50% (2, 192 km 2 ) or 25% (1, 096 km 2 ) of existing improved pasture are quantified. Across the study area as a whole, only surface run‐off with SRC planted at the 50% level was significantly impacted, where it was reduced by up to 23% (during April). However, results varied spatially and a comparison of annual means for each sub‐basin and scenario revealed surface run‐off was significantly decreased and baseflow significantly increased (by a maximum of 40%) with both Miscanthus and SRC. Evapotranspiration was significantly increased with SRC (at both planting levels) and water yield was significantly reduced with SRC (at the 50% level) by up to 5%. Effects on streamflow were limited, varying between −5% and +5% change (compared to baseline) in the majority of sub‐basins. The results suggest that for mesic temperate grasslands, adverse effects from the drying of soil and alterations to streamflow may not arise, and with surface run‐off reduced and baseflow increased, there could, depending on crop location, be potential benefits for flood and erosion mitigation. Abstract : Using the Soil & Water Assessment Tool (SWAT), we investigate changes to hydrology following land conversion of 50% and 25% of existing improved pasture in western UK to the bioenergy crop Miscanthus or short rotation coppice (SRC). Soil water content and streamflow were not significantly changed compared to the baseline scenario of existing land use. Surface run‐off was reduced for both crops (by up to 40%), whereas evapotranspiration was increased with SRC (by up to 5%), and reduced with Miscanthus (by up to 2%). Reductions in surface run‐off throughout the year could have potential benefits for flood mitigation schemes.